Ergo-Iconic Meaning-Making in Local Products: Generation Z, Digital Consumption Experience, and Consumer-Interpreted Value - Andriyansah Andriyansah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
This article examines how Generation Z interprets ergo-iconic value in local products through digital consumption experience. Although previous studies have discussed ergo-iconic value in relation to product strategy, marketing performance, SME competitiveness, social media virality, and digital product value, limited attention has been given to how this value is interpreted, negotiated, and articulated by young consumers in everyday digital consumption practices. Using a qualitative interpretive design, this study draws on in-depth interviews with 30 Generation Z consumers, digital observation of publicly available social media and marketplace content, and document analysis of product descriptions, packaging narratives, and promotional materials. The findings identify five interrelated themes: functional interpretation of ergo value, symbolic interpretation of iconic value, digital articulation of product meaning, negotiation of local identity, and the formation of an ergo-iconic meaning-making model. The study shows that ergo value is interpreted through usability, comfort, reliability, affordability, accessibility, and everyday suitability, while iconic value is interpreted through local identity, authenticity, visual distinctiveness, cultural narrative, community connection, and lifestyle relevance. Digital consumption experience functions as the space where these meanings are encountered, evaluated, displayed, reviewed, shared, criticized, and renegotiated. The article argues that ergo-iconic value is not fixed within local products or fully controlled by producers. Rather, it is produced through the interaction between product attributes, consumer interpretation, and digital circulation. The study contributes to product value theory by reframing value as an interpretive and socially circulated process, extends symbolic consumption theory by showing how identity-bearing products are articulated through digital practices, and refines ergo-iconic value as a consumer-interpreted meaning-making construct. Practically, the findings suggest that local entrepreneurs and MSMEs need to build products that are functionally credible, symbolically coherent, and digitally communicable